Rancang Bangun Sistem Informasi Tracer Study Alumni Institut Teknologi Garut Berbasis Website - Yosep Septiana; Leni Fitriani; Fakhrul Hawariyan; Rina Kurniawati; Risma Liyana Ulfa (Institut Teknologi Garut, 2023)
Alumni tracer study is a method of tracking or surveying alumni by tertiary institutions as well as private universities, the tracer study is used as a source of information and to find out the absorption process, and the position of graduates in the world of work. The Garut Institute of Technology is a tertiary institution located in Garut Regency which always produces the best undergraduate graduates from year to year the number of students continues to increase. The Garut Institute of Technology already has an alumni tracer study system, due to the limitations of the system in terms of adding variables to add question items, the tracer study alumni still use the Google form, and for questionnaires as the number of students at the Garut Institute of Technology requires a separate database and applications in its management . The purpose of this research is to design and build a tracer study information system to accelerate tracer study alumni management, and facilitate alumni data processing. This study uses the Rational Unified Process methodology with the stages of inception, elaboration, construction, and transition. Application testing uses the alpha test and beta test with the black box testing method. The results of this research are: the website-based information system for tracer study alumni of the Garut Institute of Technology makes it easy to recap the results of the tracer study questionnaire and manage alumni data, as well as access information on job vacancies for alumni.